Intravenous dexmedetomidine 1µg/kg as premedication to attenuate hemodynamic response to laryngoscopy and endotracheal intubation in surgeries under general anesthesia - Modh, Dixitkumar B.; Gohil, Pratiti; Parmar, Manthan (International Surgery Journal, 2017)
Background: Choice of premedication and hemodynamic stability are always remain important concerns during laryngoscopy and endotracheal intubation for Anesthesiologists. Dexmedetomidine offers anxiolytic, sedation, hypnosis, analgesia, antisialagogue action as well as sympatholysis which make most suitable drug as premedication. Our aims for this study to evaluate efficacy of Injection Dexmedetomidine 1µg/kg intravenously as premedication on attenuation of hemodynamic changes to laryngoscopy and intubation as well as requirement of injection Propofol as an induction agent. Methods: In Present study, 60 patients of ASA I, II of age 18 to 45 years were randomly divided in to two groups of 30 each. In group NS, 10 ml normal saline and in group D1 injection Dexmedetomidine 1µg/kg diluted in 10 ml of normal saline was used. In both groups study solutions administered over 10 minutes. Both the groups were administered standard general anaesthesia and requirement of Propofol was noted as an induction agent. Heart rate, blood pressure (systolic, diastolic and mean arterial pressure) were compared at baseline, 2 min, 5 min, 10 minutes (SD2, SD5, SD10) after study drugs administration, before induction (BI), after induction (AI), 1 minute (T1), 2 minutes (T2), 5 minutes (T5) and 10 minutes (T10) after laryngoscopy and intubation in both groups. Results: HR, SBP, DBP and MAP highly significantly reduced at 2 min, 5 min and 10 minutes after infusion of Dexmedetomidine in group D1 as compared to group NS. (P<0.01). After induction values are highly significant in group D1 than group NS from baseline (P<0.01). Highly significant mean rise in hemodynamic parameters (HR, SBP, DBP and MAP) from baseline were observed in group NS compared to group D1 after laryngoscopy and intubation (P<0.01). Induction dose requirement of inj. Propofol significantly reduced in group D1 compared to other group (P<0.01). Conclusions: Injection Dexmedetomidine 1µg/kg provides effective and complete attenuation of pressure response to laryngoscopy and endotracheal intubation as premedication with decreased requirement of inj. Propofol for induction without any side effects.